Challenges with Breastfeeding: Pain, Nipple Trauma, and Perceived Insufficient Milk Supply. Issue 3 (May 2023) - Mahurin-Smith, Jamie
Abstract: Background and Significance: Breastfeeding problems are common; however, health care providers vary widely in their ability to address them effectively. Purpose: The purpose of this study was to identify the relative frequencies of common breastfeeding challenges and their associations with maternal well-being. Study Design and Methods: Women completed an online survey in which they described breastfeeding problems. Factor analysis was used to identify problems that co-occurred frequently, as well as the problems most strongly associated with maternal distress, maternal perceptions of greater severity, and postpartum depression or postpartum anxiety. Results: There were 535 responses to the online survey; of these, 457 answered the question about the nature of their breastfeeding difficulties. Pain with breastfeeding was the most common breastfeeding problem. Difficulties with milk supply and milk intake were most strongly associated with heightened maternal distress and perceptions of severity. Clinical Implications: Coordinated care for breastfeeding dyads, in which providers acknowledge the complex and reciprocal nature of many breastfeeding problems, has the potential to improve maternal satisfaction with breastfeeding as well as breastfeeding metrics. Abstract : Breastfeeding challenges are common. In this study of over 450 new mothers who were recruited from social media, breastfeeding pain, nipple trauma, and perceived insufficient milk supply were the most frequently reported barriers to women reaching their breastfeeding goals. Nurses can use these data to advise women what to expect during breastfeeding and offer options prospectively that may help to avoid some of these situations.